An investigation into modal markers expressing dialogistic expansiveness in us presidents’ inauguration speeches - Đỗ Thị Mai Phương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims to investigate the modal markers expressing the dialogistic expansiveness in US Presidents’ inauguration speeches to provide Vietnamese learners of English with practical knowledge concerning the evaluative aspects and the linguistic realizations of these modal markers